Depression and adipose and serum cholesteryl ester polyunsaturated fatty acids in the survivors of the seven countries study population of Crete - Mamalakis, G; Jansen, E; Cremers, H; Kiriakakis, M; Tsibinos, G; Kafatos, A (European journal of clinical nutrition, 2006)
Background: Studies have shown that depression relates to biomarkers of both short- and long-term polyunsaturated fatty acid (PUFA) intake. However, it is not known which of these two biomarkers has the closest relationship to depression. Objective: To examine the relationship of depression with both adipose tissue and serum cholesteryl ester PUFA and to assess the importance of each of these two biomarkers in relating to depression. Design: Cross-sectional study of healthy elderly men from the island of Crete. Setting: The Preventive Medicine and Nutrition Clinic, University of Crete, Greece. Subjects: A total of 150 males, aged 80-96 years. The subjects were survivors of the Greek Seven Countries Study group. Methods: Fatty acids were determined by gas chromatography in adipose tissue and serum cholesteryl esters. Information about depression was obtained through the use of the short form of the Geriatric Depression Scale (GDS-15). Results: Regression analysis showed that depression related positively to age and serum cholesteryl ester arachidonic/docosahexaenoic fatty acid ratio. The only significant unadjusted correlation between depression and serum cholesteryl ester and adipose fatty acids was with adipose alpha-linolenic acid (ALA) (r=-0.31, P<0.01). Depressed males (GDS-15>5) had lower adipose ALA and sum n-3 fatty acids than non-depressed ones. There were no significant differences between depressed and non-depressed males in serum cholesteryl ester fatty acids. When adipose tissue ALA was included as one of the independent measures in the regression model, the observed positive relation between GDS-15 depression and cholesteryl ester rachidonic/docosahexaenoic ratio failed to persist. Instead, there was a negative relationship between GDS-15 depression and adipose tissue ALA. Conclusions: It appears that the fatty acids of the adipose tissue are better predictors of depression than those of serum cholesteryl esters. This indicates that depression relates more strongly to long-term than to short-term fatty acid intake. The reason for this may be the reported slow rate of deposition of dietary PUFA to the brain.